1989
DOI: 10.1159/000199909
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis and Classification in Acute Pancreatitis

Abstract: The clinical outcome in 52 consecutive episodes of suspected acute pancreatitis was compared with Ranson’s prognostic signs and findings on noncontrast and contrast-enhanced computed tomography (CT) scans performed within 24 h of patient admission. The predictive value of CT scan for diagnosis was 95% for positive results and 53% for negative results. In providing an accurate prognosis of a single attack, scoring of extrapancreatic signs was as good as that of Ranson’s prognostic signs. CT with contrast medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Schroder et al [18] have reported that extrapancreatic changes were more frequent in patients with hemorrhagic pancreatitis. Hjelmqvist et al [19] reported similar findings, and they suggested that peripancreatic edema, retroperitoneal and intraperitoneal edema, bowel distension, and pleural effusion should be incorporated into the scoring system. However, the prognostic value of this score using receiver operator characteristic (ROC) curve analysis was never determined.…”
Section: Introductionmentioning
confidence: 77%
“…Schroder et al [18] have reported that extrapancreatic changes were more frequent in patients with hemorrhagic pancreatitis. Hjelmqvist et al [19] reported similar findings, and they suggested that peripancreatic edema, retroperitoneal and intraperitoneal edema, bowel distension, and pleural effusion should be incorporated into the scoring system. However, the prognostic value of this score using receiver operator characteristic (ROC) curve analysis was never determined.…”
Section: Introductionmentioning
confidence: 77%
“…Although the EP score is useful and correlates with patients' prognoses, relatively many points have to be assessed. 14 In addition, some author also suggested that the EP changes especially in pararenal space paralleled the severity of acute pancreatitis. However, they also indicated that the extension of peripancreatic fluid to the splenic area did not correlate with mortality.…”
Section: Assessment Of Severity and Advantages Of Modified Ct Severitmentioning
confidence: 99%
“…Contrast enhanced computed tomography (CT) scanning has been investigated extensively because of its ability to identify local complications (pseudocyst, abscess, phlegmon, peripancreatic fluid) and necrotizing pancreatitis, both of which are thought to lead to increased morbidity and mortality. [20][21][22][23][24][25][26] The sensitivity and specificity of CT findings for the prediction of severe pancreatitis from several prospective studies is shown in Table 21.4. Although the presence of necrosis did correlate with a more complicated course, the extent of necrosis did not provide any additional prognostic value.…”
Section: Computed Tomographymentioning
confidence: 99%
“…21 88 PC/D 90 73 Grade D + E Hjelmqvist et al 22 47 PC/14-day 71 80 hospitalization London et al 23 32 D/PC/20-day 83 65 Selection bias, criteria hospitalization London et al 24 126 D/PC 71 77 Clavien et al 25 176 D/PC 66 97 Puolakkainen 26 88 66 100 For abbreviations see Table 21.2. …”
Section: Individual Laboratory Testsmentioning
confidence: 99%